2013
DOI: 10.1080/02827581.2012.679680
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variations of biomass, carbon and nitrogen of roots under different tree species

Abstract: Seasonal changes of root biomass, concentrations and masses of carbon and nitrogen in roots and root diameter classes ( B2mm, 2Á5mm and 5mm) were evaluated under four adjacent coniferous plantation sites: Oriental spruce (Picea orientalis L.), Austrian pine (Pinus nigra Arnold), Turkish fir (Abies bornmulleriana L.), Scots pine (Pinus sylvestris L.) and natural Sessile oak (Quercus petraea L.) forest.The root biomass, carbon and nitrogen concentrations, carbon and nitrogen masses, C/N ratio of roots were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…3). It is well established that fine roots are very responsive to local variation in soil fertility, even within a season (Vanguelova et al, 2005;Akburak et al, 2013). When we combined our results on roots with published data on aboveground biomass to evaluate the possible impact of several fuelwood harvest strategies on soil fertility (objective #(iii) of this study), our simulations clearly showed that harvesting complete canopies (i.e.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…3). It is well established that fine roots are very responsive to local variation in soil fertility, even within a season (Vanguelova et al, 2005;Akburak et al, 2013). When we combined our results on roots with published data on aboveground biomass to evaluate the possible impact of several fuelwood harvest strategies on soil fertility (objective #(iii) of this study), our simulations clearly showed that harvesting complete canopies (i.e.…”
Section: Discussionmentioning
confidence: 60%
“…). It is well established that fine roots are very responsive to local variation in soil fertility, even within a season (Vanguelova et al ., ; Akburak et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Annual mean precipitation is around 1091 mm, and mean annual temperature is 12.8 °C. Most of the precipitation falls between October and March (Balci et al 1986, Özhan et al 2010, Akburak et al 2013.…”
Section: Seedling Growth and Radicle Pruningmentioning
confidence: 99%
“…This upscaling does not take into account the seasonal variability in above and below standing biomass and N concentration. Based on the studies of Ceccon et al (2011) and Akburak et al (2012), the increase of N content in roots late in the growing season can partly compensate the parallel increment of N content in the AG biomass. Additional measurements of N and C content along the season would be required to shed light on the internal cycling of these elements and to reduce uncertainties in computation of this scaling factor.…”
Section: R a Assessmentmentioning
confidence: 99%